Acute effects of stretching on flexibility and performance: A narrative review - Lima, C. D.; Ruas, C. V.; Behm, D. G.; Brown, L. E. (Journal of Science in Sport and Exercise, 2019)
Passive and active stretching techniques have been shown to increase both chronic and acute range of motion (ROM). Acute ROM improvements can be countered by decreases in muscle performance, primarily after prolonged static stretching (SS) and proprioceptive neuromuscular facilitation (PNF) techniques when not incorporated into a full warm up procedure. In contrast, ballistic stretching and dynamic stretching techniques typically induce either an increase or no change in muscular force and power. This review explores studies that have investigated stretching responses on ROM, muscle functionality and performance. Collectively, the literature demonstrates that prolonged acute SS and PNF stretching can elicit the greatest changes in flexibility, but without additional dynamic activities (i.e. full warm up) can induce neuromuscular force and power output impairments, while increasing ROM and some sports specific performance. Muscle response to stretching may be determined by the manipulation of confounding variables such as duration, population, volume, test specificity and frequency. An increased dosage of some of these variables during stretching in isolation, augments ROM increases while attenuating muscle force output, except for stretching intensity which may lead to similar responses. Populations with high flexibility may have positive effects from stretching when tested on their sport specific performance, while general population may suffer greater negative effects. Not controlling these variables during stretching protocols may lead to misleading information regarding its effects on muscle performance.